Strategy to Accelerate Bureaucratic Reform Towards a Golden Indonesia 2045 - Radit Saputra; Irfandi Pratama (Journal of Governance and Spatial Planning, 2025)
strategy of accelerating bureaucratic reform as the main pillar in realizing the vision of a Golden Indonesia 2045. Adaptive, responsive, and technology-based bureaucratic reform is key to creating effective and globally competitive governance. The study uses a descriptive qualitative approach with secondary data sources from the relevant literature. The proposed strategy includes three levels of bureaucratic transformation: macro (institutional structure reform), meso (strengthening the governance architecture through SPBE), and micro (individual capacity development and ASN talent management). The implementation of the Electronic-Based Government System (SPBE) is considered an important instrument in supporting efficient and accountable public services. The case study of Polewali Mandar Regency shows good practices in the implementation of SPBE in the eastern region of Indonesia. In addition, ASN talent management is an important strategy in forming a professional and innovative bureaucracy. The results of the analysis confirm that structured and comprehensive bureaucratic reform is needed to achieve the national development goals as designed in the 2025–2029 RPJMN, towards an inclusive, sustainable, and progressive Indonesia.